Politeness strategies employed by teachers in making requests to eleventh-grade students - Tinanthy Rosse Santosa; Ayang Winda; Shadam Hussaeni Pratama (Concept : Community Concern for English Pedagogy and Teaching, 2023)
This study aims to find the types of politeness strategies used and the implications of using politeness strategies in the teaching and learning process by using the theory of Brown and Levinson (1987). This study used qualitative research with descriptive analysis with eleventh-grade students as the participants. As a result, there were four types of politeness strategies that occurred when the teacher made a request: bald on record, positive politeness, negative politeness, and off record. .According to the statistics, the most prevalent politeness method utilised by teachers in making requests was the bald-on-record strategy. A bald-on record technique was employed since the idea presented became clearer and unequivocal, and it did not take long for pupils to understand.. While the least was off record because the utterances with this strategy were considered to be unclear and ambiguous, and not all students could interpret the meaning of the utterance,. This study also found out the implications of using politeness strategies, which were effective communication, cooperative interaction, and less imposition. Besides, the result can be used as evaluation material for teachers and schools in using politeness strategies to persuade the students to fulfil the request. Keywords : Politeness strategies; requesting; teaching learning process